2021
DOI: 10.1186/s12913-021-06209-6
|View full text |Cite
|
Sign up to set email alerts
|

“The staff are not motivated anymore”: Health care worker perspectives on the Integrated Management of Childhood Illness (IMCI) program in the Philippines

Abstract: Background Studies focusing on the Integrated Management of Childhood Illness (IMCI) program in the Philippines are limited, and perspectives of frontline health care workers (HCWs) are largely absent in relation to the introduction and current implementation of the program. Here, we describe the operational challenges and opportunities described by HCWs implementing IMCI in five regions of the Philippines. These perspectives can provide insights into how IMCI can be strengthened as the program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Selfdirected learning was delivered via course modules, IMCI chart booklets, educative CDs/DVDs, photographic books, logbooks and exam sheets. Our findings largely reflect what has been documented in previous literature on implementation of DIMCI in Tanzania [2,[21][22][23].…”
Section: The Delivery Of the Dimci: Structure Organization Contents A...supporting
confidence: 89%
“…Selfdirected learning was delivered via course modules, IMCI chart booklets, educative CDs/DVDs, photographic books, logbooks and exam sheets. Our findings largely reflect what has been documented in previous literature on implementation of DIMCI in Tanzania [2,[21][22][23].…”
Section: The Delivery Of the Dimci: Structure Organization Contents A...supporting
confidence: 89%
“…Our current study shows that some healthcare workers in the Ashanti Region of Ghana have inadequate skills and training in using mHealth apps for disease screening and treating conditions. These findings have been shown in other resource-limited settings where some healthcare workers have insufficient training and skills to use mHealth applications to promote healthcare access [46][47][48]. In these studies, despite the insufficient training and skills, healthcare professionals intimated that mHealth applications such as text messages and mHealth apps are very useful.…”
Section: Plos Onementioning
confidence: 70%
“…A recent study in the Philippines echoed the same sentiments regarding the rejection of parental concerns by HCWs, leaving the parent scared and embarrassed to voice vaccine‐related concerns [29]. Several studies suggested that HCWs were overburdened, hence the burnout and demotivation phenomenon, reflecting the current tenor in the literature [52–54], but evidence of retention strategies, incentives, and other professional support is so far limited. Our findings also highlighted how social media altered communication and stoked widespread anxieties that permeated other contexts [55–57].…”
Section: Discussionmentioning
confidence: 99%